2018
DOI: 10.1111/jocd.12773
|View full text |Cite
|
Sign up to set email alerts
|

A survey on usage of personal care products especially cosmetics among university students in Saudi Arabia

Abstract: The usage of cosmetics was found to be extremely high among the college going Saudi students in Wadi Al Dawasir Region, Kingdom of Saudi Arabia. Un-awareness regarding the harmful effects of cosmetics was found to be high among these students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 4 publications
3
21
0
2
Order By: Relevance
“…For example, Saudi females spend more on makeup as compared to women in the Arab world, the West, and the Gulf. According to an estimate, statistics issued by Saudi customs suggest that the number of imported cosmetics in the past year exceeded SR2.3 billion 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Saudi females spend more on makeup as compared to women in the Arab world, the West, and the Gulf. According to an estimate, statistics issued by Saudi customs suggest that the number of imported cosmetics in the past year exceeded SR2.3 billion 20 …”
Section: Discussionmentioning
confidence: 99%
“…According to an estimate, statistics issued by Saudi customs suggest that the number of imported cosmetics in the past year exceeded SR2.3 billion. 20 The consumption patterns of cosmetics in the Arab population are remarkable. The mean age of participants who use cosmetics is 34 years old, typically a fairly grown adult.…”
Section: Ta B L E 4 Association Between the Skin Type And Tone With T...mentioning
confidence: 99%
“…Mombeini et al, noted that many participants in their study were unfamiliar with organic product terms 7 . A study among University students in Saudi Arabia demonstrated that about 66% of the students were aware of the presence of different chemicals in the cosmetics they use on a daily basis 8 . In a study conducted among beach visitors in Hawaii, 75% of the participants were aware of the harmful effects of chemicals in sunscreen, but one third of them continued to use the same 9 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also noted that there is a lack of knowledge regarding the composition and harmful effects, if any of the cosmetics used by the subjects 7,8 . Lack of shops catering to organic cosmetics was also noted to be a factor 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Pemalsuan produk kosmetik ataupun kosmetik juga rentan dilakukan oleh produsenprodusen nakal terhadap produk yang telah teruji baik oleh BPOM sehingga dapat membuat citra buruk dari produsen produk itu. Penyalahgunaan ini dapat membuat kerugian bagi konsumen atau masyarakat yang telah percaya dengan produk itu tetapi dengan iming-iming harga murah masyarakat jadi membeli produk palsu itu dan berakibat pada rusaknya kulit tubuh dan wajah masyarakat (Husain, 2019).…”
Section: Pendahuluanunclassified